Advance in strategies to build efficient vaccines against tuberculosis - Qu, Wei; Guo, Yinhui; Xu, Yan; Zhang, Jie; Wang, Zongchao; Ding, Chaoyue; Pan, Yuanhu (Frontiers in Veterinary Science, 2022)
Tuberculosis is a chronic consumptive infectious disease, which can cause great damage to human and animal health all over the world. The emergence of multi-drug resistant strains, the unstable protective effect of Bacillus Calmette-Guérin (BCG) vaccine on adults, and the mixed infection with HIV all warn people to exploit new approaches for conquering tuberculosis. At present, there has been significant progress in developing tuberculosis vaccines, such as improved BCG vaccine, subunit vaccine, DNA vaccine and live attenuated vaccine. Among these candidate vaccines, there are some promising vaccines to improve or replace BCG vaccine effect. Meanwhile, the application of adjuvants, prime-boost strategy, immunoinformatic tools and targeting components have been studied concentratedly, and verified as valid means of raising the efficiency of tuberculosis vaccines as well. In this paper, the latest advance of tuberculosis vaccines in recent years is reviewed to provide reliable information for future tuberculosis prevention and treatment.